Enablers and Barriers to Implementing ICU Follow-Up Clinics and Peer Support Groups Following Critical Illness: The Thrive Collaboratives*. Issue 9 (September 2019) - Haines, Kimberley J.; McPeake, Joanne; Hibbert, Elizabeth; Boehm, Leanne M.; Aparanji, Krishna; Bakhru, Rita N.; Bastin, Anthony J.; Beesley, Sarah J.; Beveridge, Lynne; Butcher, Brad W.; Drumright, Kelly; Eaton, Tammy L.; et al.
Abstract : Objectives: Data are lacking regarding implementation of novel strategies such as follow-up clinics and peer support groups, to reduce the burden of postintensive care syndrome. We sought to discover enablers that helped hospital-based clinicians establish post-ICU clinics and peer support programs, and identify barriers that challenged them. Design: Qualitative inquiry. The Consolidated Framework for Implementation Research was used to organize and analyze data. Setting: Two learning collaboratives (ICU follow-up clinics and peer support groups), representing 21 sites, across three continents. Subjects: Clinicians from 21 sites. Measurement and Main Results: Ten enablers and nine barriers to implementation of "ICU follow-up clinics" were described. A key enabler to generate support for clinics was providing insight into the human experience of survivorship, to obtain interest from hospital administrators. Significant barriers included patient and family lack of access to clinics and clinic funding. Nine enablers and five barriers to the implementation of "peer support groups" were identified. Key enablers included developing infrastructure to support successful operationalization of this complex intervention, flexibility about when peer support should be offered, belonging to the international learning collaborative. Significant barriers related to limited attendance by patients and families due to challenges in creating awareness, and uncertainty about who might be appropriate to attend and target in advertising. Conclusions: Several enablers and barriers to implementing ICU follow-up clinics and peer support groups should be taken into account and leveraged to improve ICU recovery. Among the most important enablers are motivated clinician leaders who persist to find a path forward despite obstacles. Abstract : Supplemental Digital Content is available in the text.